2004
DOI: 10.2355/isijinternational.44.1480
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Manganese Oxides by Methane-containing Gas

Abstract: The paper presents results of reduction of pure manganese oxides by methane containing gas in nonisothermal and isothermal experiments and reduction mechanisms. The extent and rate of manganese oxide reduction were determined by on-line off-gas analysis using a mass-spectrometer in a fixed bed laboratory reactor in the temperature range 1 000-1 200°C at different gas compositions.Manganese oxides were reduced to carbide Mn 7 C 3 . High extent and rate of reduction by methane-containing gas in comparison with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Our experimental study of direct reduction of quartz or amorphous silica powder by methane demonstrated that intermediate product SiO vapor escaped from the reaction zone as fume during reaction without conversion to SiC. This problem is not encountered in reduction of other metal oxides by methane as their intermediates are in the form of metals (Fe [17,18] ) or solid suboxides (Mn x O y [15] and Ti x O y [14] ) which are further converted to metal carbides by reacting with methane or deposited carbon. The gaseous SiO can be ''caught'' providing an intimate contact of quartz with solid carbon either by chemical vapor deposition from methane in silica particles before reduction [20] or by mechanical mixing of carbon and silica.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Our experimental study of direct reduction of quartz or amorphous silica powder by methane demonstrated that intermediate product SiO vapor escaped from the reaction zone as fume during reaction without conversion to SiC. This problem is not encountered in reduction of other metal oxides by methane as their intermediates are in the form of metals (Fe [17,18] ) or solid suboxides (Mn x O y [15] and Ti x O y [14] ) which are further converted to metal carbides by reacting with methane or deposited carbon. The gaseous SiO can be ''caught'' providing an intimate contact of quartz with solid carbon either by chemical vapor deposition from methane in silica particles before reduction [20] or by mechanical mixing of carbon and silica.…”
mentioning
confidence: 82%
“…Solid carbon deposited on the sample surface by Reaction [15], hindering the further progress of reduction by blocking the particles' surface and preventing carbon supply for further reduction to the pellet's interior.…”
Section: þ; ½14mentioning
confidence: 99%
See 3 more Smart Citations